PENDIDIKAN SEBAGAI INVESTASI SUMBER DAYA MANUSIA: ANALISIS DATA ANNUAL REPORT SEKOLAH ALAM INDONESIA CIPEDAK TAHUN AJARAN 2023–2024 - Hindarsih, Tri Puji; Ratnaningsih, Sita (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to analyze education as a form of human capital investment using empirical data from the Annual Report of Sekolah Alam Indonesia (SAI) Cipedak for the 2023–2024 academic year. The analysis focuses on five key indicators of educational investment. These include program implementation, student character and soft skill development, literacy and numeracy outcomes, teacher development, and the structure of educational costs. The study uses a descriptive qualitative and quantitative approach based on secondary data. The findings show that program implementation reached 98 percent. Literacy and numeracy performance increased consistently over the past three years. Character assessment covered three domains. These include moral values, leadership, and thinking skills. The cost structure shows major allocation to teacher development and learning programs. These results indicate that education at SAI Cipedak generates significant academic and non-academic benefits and provides measurable investment returns through improved student competencies and learning quality. The findings also reinforce the theoretical perspective that education functions as a core mechanism for building human capital. The study implies that schools should strengthen financial planning and teacher-development strategies to maximize the long-term value of educational investment.